Pelatihan Penyusunan Bahan Ajar Podcast Pendidikan Pancasila dan Kewarganegaraan Berbasis Aplikasi Anchor - Dian Agus Ruchliyadi; Dedy Ari Nugroho; Akbar Akbar; Mursidah Mursidah (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
Technology in the era of society 5.0 is an important aspect that needs more attention so that it can be directed at achieving progress. This service focuses on responding to the progress of the times and the needs of today's learning, where application innovation is needed. One aspect that determines the success of learning is the availability of teaching materials that are accessible to users. The innovation of the anchor application in providing teaching materials for the Pancasila and Citizenship Education podcast has become the focus of this study. Innovative activities contain issues and focus of service, goals of service, research methods/approaches/strategies. Training and socialization of the importance of innovation in education through anchor applications is one of the very possible momentums to be developed. Making learning content that is easily accessible and can increase students' interest in learning the material needs to be presented in a more innovative form. The anchor application training and socialization will be implemented at SMP Negeri 1 Anjir Muara Barito Kuala. The school was selected with data that teachers and students have facilities that allow them to use the anchor application on smartphones. The service was carried out on July 2, 2022 at SMP Negeri 1 Anjir Muara Barito Kuala.